PENGUATAN KEMAMPUAN BERNALAR KRITIS MATEMATIS SISWA SMP PADA PEMBELAJARAN MENDALAM BERMUATAN ETNOMATEMATIKA MAJAPAHIT PADA MATERI KESEBANGUNAN - Azmi, Mei Putri Ilul; Deka Anjariyah; Feriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe teacher activities, student activities, and students' mathematical critical reasoning ability after the implementation of deep learning integrated with Majapahit ethnomathematics on similarity material. The low critical reasoning ability of junior high school students, reflected in an initial test mean score of only 35.89, far below the minimum mastery criteria of 78, became the background of this study. The research used a quantitative descriptive method with a One Shot Case Study design. The sample consisted of 32 students of class VII-A at SMP Negeri 2 Puri, selected through Simple Random Sampling. Data were collected through observation and a mathematical critical reasoning test referring to four indicators: obtaining and processing information, analyzing information, reflecting on thinking, and decision making. The results showed that teacher activity reached 86.6% and student activity reached 96.6%, both in the very good category. The critical reasoning test results showed that 6 students (18.7%) were in the high category, 21 students (65.6%) in the moderate category, and 5 students (15.6%) in the low category, with an overall mean score of 73.82. The highest indicator mean was obtaining and processing information (3.7), while the lowest was decision making (1.9). These findings indicate that the implementation of deep learning integrated with Majapahit ethnomathematics can support students' mathematical critical reasoning ability.